Uji Efektivitas Ekstrak Daun Kipahit (Tithonia diversifolia) Terhadap Mortalitas dan Intensitas Serangan Keong Mas (Pomacea canaliculata L.) Pada Tanaman Padi (Oryza sativa L.) Varietas Inpari 32 - Nirmala Putri Maharani Setiakusuma; Lutfi Afifah; Sugiarto Sugiarto; Anton Yustiano (JURNAL AGROPLASMA, 2023)
Paddy (Oryza sativa L.) is a staple food crop and the primary source of fuel for the Indonesian economy. One of the many strategies that needs to be developed to decrease yield loss is pest control for rice. An extremely problematic pest of rice crops is the golden snail (Pomacea canaliculata L.). The golden snail attack on rice plants has the potential to reduce yields and even fail to harvest. In most cases, chemical pesticides are still used to control golden snails, but their overuse can lead to pest resistance. The objective of this research was to identify Kipahit leaf extract (Tithonia diversifolia) concentrations effective in reducing golden snail P.canaliculat) mortality and attack intensity on Inpari 32 rice varieties. The study employed a Randomised Block Design (RAK) with 5 replicates and 6 treatments to examine a single factor. Treatment levels A (Control/No Treatment), B (Kipahit Leaf Extract 40 g/L), C (Kipahit Leaf Extract 50 g/L), D (Kipahit Leaf Extract 60 g/L), E (Kipahit Leaf Extract 70 g/L) and F (Kipahit Leaf Extract 80 g/L) had a significant effect on mortality and intensity of golden snail P.canaliculat attack on plants rice (Oryza sativa L.) Inpari 32 variety. Treatment F (80 g/L Kipahit leaf extract) resulted in the highest mortality rate (74.00%) and the weakest attack intensity (59.67%).